2000
DOI: 10.1002/(sici)1097-4601(2000)32:6<378::aid-kin4>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

The solvent effects in the reactions of carboxylic acids with oxiranes. 1. Kinetics of the reaction of acetic acid with epichlorohydrin in butan-1-ol

Abstract: Kinetics of the reaction of acetic acid with epichlorohydrin in the presence of chromium(III) acetate in butan-1-ol solution have been studied. The partial reaction orders with respect to reagents were found. The reactions were of first-order with respect to both epichlorohydrin and catalyst and zeroth order with respect to acetic acid. A kinetic model for the overall process has been proposed. The reaction constants have been calculated along with the activation parameters. The effect of dilution on the rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…Both in bulk8 and in the presence of butanol,11 the kinetics of reaction between acetic acid and epichlorohydrin are well described by the set of differential equations where the reaction is of the first order with respect to both ECH and catalyst, and zero order with respect to AA. where k 1 is the rate constant of addition of acetic acid to epichlorohydrin and k 2 is the overall rate constant of all side reactions involving epichlorohydrin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both in bulk8 and in the presence of butanol,11 the kinetics of reaction between acetic acid and epichlorohydrin are well described by the set of differential equations where the reaction is of the first order with respect to both ECH and catalyst, and zero order with respect to AA. where k 1 is the rate constant of addition of acetic acid to epichlorohydrin and k 2 is the overall rate constant of all side reactions involving epichlorohydrin.…”
Section: Resultsmentioning
confidence: 99%
“…A change of reaction environment may therefore affect the rates at which individual products are formed. Dilution of the reaction mixture containing chromium(III) acetate with a protonic solvent (butanol) has resulted in a change of both reaction rate and selectivity 11. This suggested that the presence of reaction product may also affect the rate of addition of carboxylic acid to oxiranes carried out in the presence of chromium(III) catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of a donor substance may, due to donor−acceptor interactions, lead to changes in the catalytic activity. Specifically, while studying the reaction of acetic acid with epichlorohydrin, we have found that gradual dilution of the system with a protic solvent, butanol, initially reduced the rate of addition, but as the dilution increased, the rate constant of the reaction increased again . Substantial dilution of the system with butanol did not affect the regioselectivity of reaction; however, side reactions involving epichlorohydrin intensified, and up to 10% of the oxirane was wasted in side reactions.…”
Section: Introdutionmentioning
confidence: 99%
“…We have found in our previous studies that the addition of carboxylic acids to oxiranes is effectively catalysed by chromium(III) ethanoate. The catalyst strongly differentiates between the abilities of hydroxyl groups of an acid and alcohol to react with oxiranes. Hence, in the presence of Cr(AcO) 3 , the substituted derivatives of ethylene oxide, such as epichlorohydrin, react with acids with high selectivity and regioselectivity.…”
Section: Introdutionmentioning
confidence: 99%
“…High conversions were obtained with homogeneous catalysts such as tertiary amines and quaternary ammonium salts, but in these cases high amounts of by-products resulted [4,5]. The highest yields and selectivity were obtained when chromium salts of involved acids were used in esterification reaction [6][7][8][9][10][11][12][13][14][15][16]. The difficulties that occur when these catalysts are separated from the reaction mixture represents their major drawback.…”
Section: Introductionmentioning
confidence: 99%